Emerging roles of fibroblast growth factor 21 in critical disease - Yan, Fang; Yuan, Li; Yang, Fan; Wu, Guicheng; Jiang, Xiaobo (Frontiers in Cardiovascular Medicine, 2022)
In spite of the great progress in the management of critical disease in recent years, its associated prevalence and mortality of multiple organ failure still remains high. As an endocrine hormone, fibroblast growth factor 21 (FGF21) functions to maintain homeostasis in the whole body. Recent researches have proved that FGF21 has promising potential effects in critical diseases. FGF21 has also been found to have a close relationship with the progression of critical diseases and has a great predictive function for organ failure. The level of FGF21 was elevated in both mouse models and human patients with sepsis or other critical illnesses. Moreover, it is a promising biomarker and has certain therapeutic roles in some critical diseases. We will focus on the emerging roles of FGF21 and its potential effects in critical diseases including acute lung injury/acute respiratory distress syndrome (ALI/ARDS), acute myocardial injury (AMI), acute kidney injury (AKI), sepsis and liver failure in this review. FGF21 has high application value and is worth further studying. Focusing on FGF21 may provide a new perspective for the management of critical disease.